K Nearest Neighbor Path Queries Based on Road Networks - Lulin Chen; Guofeng Qin (Institute of Advanced Engineering and Science, 2013)
The Island is a k nearest neighbor query algorithm of moving objects based on road networks and can effectively balance the performance of query and update. But the algorithm doesn’t consider the direction of moving object which is required in many scenarios. It traverses vertexes from all directions, meaning wasting a lot of time in visiting useless vertexes. Besides, it doesn’t return query path. In this paper, we propose an improved Island algorithm which takes full account of moving direction. It takes best point estimate and heuristic search method, effectively reducing the number of traversal vertexes. At the same time, we optimize the data structure and let it return the query path. Results show that the improved algorithm outperforms the original one. Finally, we describe electric vehicle charging guidance system based on the improved Island algorithm. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3509